Far better than nothing at all: Towards a contingency-based evaluation of management consulting services - Andreas Ehrhardt; Michael Nippa (Technische Universität Bergakademie Freiberg, Fakultät für Wirtschaftswissenschaften, 2005)
The evaluation of consulting services is a widely, but controversially discussed issue. While there is obviously an increasing need for appropriate evaluation, there are critics questioning the applicability of evaluation methods as well as the motivation to assess. We provide a framework that can be used to improve project evaluations and structures future academic and practical discussions as it integrates relevant contingency factors (project type, consultant-client-relationship, characteristics of the evaluator) that affect opportunities and abilities to evaluate project input, throughput, and output. We summarize the prospects and challenges for the research agenda and suggest some management implications.
Keywords: L22; L23; M21; 330; Management consulting; evaluation; performance; contingency factors